Análise dos polimorfismos gênicos M235T do Angiotensinogênio aumano, GLU-298-ASP e t 786 ->C da EENOS na aipertensão e no infarto agudo do miocárdio - Gatti, Renata Ríspoli (2003)
Systemic arterial hypertension (SAH) is the leading cause of cardiovascular morbidity and mortality with a prevalence of about 25-30% in the adult Caucasian population. The primary determinants of hypertension, which represent 95% of the hypertensive population, have not been fully elucidated in the numerous investigations into the various mechanisms involved in regulating blood pressure. Knowledge of the physiological systems acting on pressure regulation offers opportunities to examine the possible role of variations in specific candidate genes in the pathogenesis of human hypertension. Many studies report that hypertensive subjects consistently have high total cholesterol, body mass index (BMI), heart rate, blood glucose and triglycerides. In previous studies, it has been observed that hypertension usually occurs in conjunction with other metabolically linked risk factors. Chronic or moderate elevations in Angll levels may increase vascular tone promoting the development of hypertension. A high concentration of angiotensinogen (TFA) in the circulation does not constitute excess substrate for the cleaved renin that acts at approximately half its maximum velocity, indicating considerable reserve potential in this reaction. Consequently, an increase in plasma or tissue AGT concentration associated with specific structural variations in AGT may result in increased baseline of Angll. The human AGT M235T polymorphism may allow the identification of individuals who are more likely to develop coronary artery disease (CAD) or acute myocardial infarction (AMI). Genotype determination can be used to understand the risks of developing these pathologies and to select individuals who may benefit from preventive intervention. Balance and interactions between vasoconstrictor and vasodilator substances is a critical factor in regulating pressure, coronary blood flowXV and cardiovascular and renal injuries. The At2 receptor plays an important role in stimulating Ang11 to produce vasodilating substances, including bradykinin and NO.